Optimism in important spheres of life among young women and men - Stojanowska, Elżbieta (Studia Psychologica: Theoria et praxis, 2003)
The research concerns optimism level in the sphere of job, health and interpersonal relationships among young women and men. The subjects were male (N = 670), and female students (385), also girls from the final classes of secondary school (240). The optimism was investigated in a form of subjective chances of avoiding negative events like unemployment, serious illness, and loneliness. In addition, a declared effort made in avoiding those traumatic events was measured. The obtained results showed that women compared with men were more optimistic in interpersonal relationships, and men were more optimistic (than women) in the sphere of job. In all the investigated areas women in comparison with men declared the stronger effort. Only among women were positive correlations between chances and declared effort in the suitable areas obtained. Girls from secondary school compared with female students disclosed weaker optimism in all the investigated spheres of life. The obtained differences between young women and m   are discussed in the context of personality and social conditions.